How Influencer Attributes Drive Online Purchase Intention Through Value Co-Creation: Evidence from the SOR Framework: English - Cesilia Felicia Laura Toda; Yolanda Masnita; Husna Leila Yusran (Program Magister Manajemen Universitas Bhayangkara Surabaya, 2026)
This study aims to analyze the influence of personal influencer attributes such as Inspiration, Similarity, and Enjoyability on consumer behavior through Value Co-Creation (VCC) and Relationship Quality (RQ). Based on the Stimulus–Organism–Response (SOR) framework, a quantitative approach was used by distributing an online questionnaire to 121 respondents aged 17–31 years, and the data were analyzed using SEM–AMOS. The results show that Inspiration has a positive effect on VCC, while Similarity increases Relationship Quality, but Enjoyability has no significant effect. Furthermore, VCC was found to strengthen RQ, which in turn increases consumers’ purchase intention toward products recommended by influencers. These findings confirm that emotional closeness and collaborative engagement between followers and influencers are more important than entertainment aspects alone. Further research is recommended to expand the influencer categories and add mediation or moderation variables to provide a more comprehensive understanding.